Reassessing project practices, research, and theory in a post-Covid reality - Pinto, Jeffrey K. (International Journal of Information Systems and Project Management, 2022)
The world is slowly emerging from a series of healthcare, financial, and economic disruptions caused by the Covid19 pandemic. While it is still too early to come to a definitive reckoning of the myriad ways in which our world has been forced to make adjustments in how it operates pre-and-post Covid, it is worth considering at least one aspect of the post-Covid reality: its effects on project management practices and theory development. This paper offers my perspective on some implications for current and future practice in project management, as well as the ways in which Covid responses have created the potential for a “new normal” in theory and formulating research questions for project studies. Drawing on the Project Management Institute’s “Global Megatrends 2022” report, I will examine these six trends and their implications for future practice in project-based work, proposing three topics for future research.